Strategi Pengurangan Kerugian Produk Kedaluwarsa Ritel Melalui Implementasi Aplikasi IoT Penjaga Inventaris Digital - Wijaya, Herri; Irawati, Fifi Endah; Akbar, Milad Nufal (Indonesian Business Review, 2026)
This study addresses inventory inefficiencies and financial losses from expired product waste in Micro, Small, and Medium Enterprises (MSMEs). Capital constraints often prevent MSMEs from adopting corporate-scale Internet of Things (IoT). We investigate a Frugal IoT approach integrated with digital nudging through a mobile application, "Penjaga Inventaris Digital." A longitudinal field experiment using a pre-test and post-test design was conducted over six months across three Amal Muhammadiyah retail outlets. Statistical testing (Paired Sample T-Test, p=0.002) demonstrated a significant 81.7% reduction in financial losses, dropping from IDR 13.25 million to IDR 2.41 million. Staff mitigation response time averaged 48.5 minutes, indicating excellent operational compliance. In conclusion, combining Frugal IoT with digital nudging effectively mitigates fast-moving consumer goods (FMCG) losses, providing strategic managerial implications for capital expenditure efficiency and data-driven retail operations.